Application of Islamic Religious Education Learning in Improving Moral Values at SDN 2 Kedung - Nova Ambaria; Mufid Mufid (Institut Muslim Cendekia, 2026)
This study holds significant academic and practical utility as it contributes to nurturing a generation with strong ethical character amid the declining morality of students. The primary objective is to examine the application of Islamic Religious Education (PAI) values and their subsequent impact on student quality and moral development at SDN 2 Kedung. Using a qualitative approach, the research identifies core values such as honesty, discipline, tolerance, and compassion, while simultaneously exploring pedagogical challenges encountered by educators in consistenly instilling these values. The empirical findings reveal that systematic operationalization of Islamic values not only deepens students’ religious understanding but also plays a crucial role in catalyzing character formation and moral literacy, particularly specific barries at the public elementary school level. Policy implications include evidence-based recommendations such as enhacing PAI teacher training, designing synthesized values-based instructional modules, and establishing ongoing regulation supervision by municipal education authorities to systematically institutionalize religious values in students’ daily lives.